Responsible management education : some voices from Asia - Swamy, Ranjini (New York, New York : Business Expert Press, 2017)
Asia is home to a very large number of business schools. This edited collection emerged from the need to know about how business schools in Asia are inculcating Responsible Management. The book describes how some Asian business schools are incorporating ethics, social responsibility, and sustainability into their curricular and extra-curricular activities. It identifies the challenges faced in providing such education and the implications thereof. In the process it captures the unique flavor of Asian business schools. Data for the book was sourced from the workshop proceedings of the 6th PRME Asia Forum held in Goa, India in November 2015 and from case studies submitted before the Forum. The Workshop sessions were a demonstration-cum-discussion about the design and conduct of some courses on responsible management. The sessions were led by faculty members from (a) public autonomous institutes such as the Indian Institute of Management, Ahmedabad; (b) private autonomous institutes such as XLRI, Jamshedpur and MDI, Gurgaon; and (c) university departments such as The School of Economics and Management at Tsinghua University in China. Some of the case studies detail the curricular interventions introduced by some business schools to inculcate responsible management. Others share the experiences of faculty members in designing and conducting specific courses/modules on responsible management, the challenges experienced in inculcating responsible management and responses. The authors are faculty members/administrators representing the Indira School of Business Studies, Pune, India; the Hang Seng Management College, Hong Kong; the Colegio de San Juan de Letran Calamba, Philippines; the Indian Institute of Management, Indore, India; the KIIT School of Rural Management, Orissa, India; and the Department of Management Studies at a University in western India. Together the workshop proceedings and the case studies suggest that the sampled Asian business schools have introduced courses/modules on responsible management. However, few appear to have made responsible management a central part of business school strategy. There is need to develop a different worldview of education, one that focuses on the wellbeing of the planet and people, rather than the wellbeing of business alone. Support from other stakeholders is critical for this to occur. Additionally, faculty members require training and encouragement to integrate responsible management in their research agendas and courses.
The six principles of PRME -- 1. Responsible management: drivers and responses discussed at the Pre-Forum Workshop in the PRME Asia Forum / Ranjini Swamy -- Part I. Case studies on institute-level interventions to promote responsible management -- 2. Indira School of Business Studies in Pursuit of Responsible Management Education / Renu Bhargava and B.S. Guha -- 3. The Colegio De San Juan De Letran Calamba, Philippines: nurturing and shaping professionals toward social orientation and care of creations / Ruel V. Maningas, Melchor C. Morandarte and Engr. Reynaldo R. Robles -- 4. The Centre For Corporate Sustainability and Innovations, Hang Seng Management College, Hong Kong / Shirley Mo-Ching Yeung -- Part II. Case studies on course-level interventions to promote responsible management -- 5. Responsible Management Education: Course-level Interventions Discussed at the Pre-Forum Workshop in the 6th PRME Asia Forum / Ranjini Swamy -- 6. Course on Marketing Ethics at the Indian Institute of Management, Indore: a reflection / Jayasankar Ramanathan and Biswanath Swain -- 7. Teaching ethics in business: experience at a University in India / Piya Mukherjee -- 8. Meeting the unmet needs of the rural poor: applying the MOIP framework in a course on rural marketing / Ajith P -- 9. Responsible management education: summary -- About the authors -- Index.
Includes index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2018. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Management -- Study and teaching (Higher); Ethics; Asia; Electronic books